(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to measure the impact of leadership practices in their various dimensions (ideal, spreading a shared vision, exploiting opportunities, encouraging individual and group initiatives, support and motivation) on the success of projects in their dimensions (project efficiency, customer impact, work success, and future readiness) in the NEOM project. The study relied on the descriptive analytical method, and the study sample consisted of 275 items. The SPSS program was used to analyze the data. The study reached several main results, most notably: There is a statistically significant impact of leadership practices in their dimensions (ideal, spreading a shared vision, exploiting opportunities, encouraging individual and group initiatives, support and motivation) on the success of projects in their dimensions (project efficiency, customer impact, work success, future readiness) in the NEOM project. The study recommended the need to develop comprehensive incentive programs aimed at motivating employees and enhancing their performance, including financial and moral rewards and appreciating individual and group achievements. It also recommended organizing periodic meetings and meetings to discuss progress towards achieving the shared vision and exchanging ideas and suggestions among all team members.